VERIFICATION OF ASSESSMENT SCALES OF THE SENSORY ENRICHED ENVIRONMENT ECERS-R AND SSTEW OR IMPLEMENTATION IN UKRAINE - Kruty, Kateryna; Holiuk, Oksana; Rodiuk, Nataliia; Popovych, Oksana; Zdanevych, Larysa; Bilska, Olha; Pakhalchuk, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The quality of education in general and preschool education in particular remains relevant both in the light of current reforms in the educational sphere of Ukraine and in the international context. Scientists pay attention to solving the problem of organizing comfortable environment, in particular the lack of internal space for each child. So far, the problems of teaching educators of preschooleducation establishments for the assessment of a high-quality sensory enriched environment have not been fully resolved. The purpose of the article is to determinate the effective quality scales of preschool education, to verify the most acceptable scales for assessment of the sensory enriched environment, to compare analysis of the obtained experimental data. During the research we used the following methods: observation, analysis, interviews, mathematical statistics, scales ECERS-R (Early Childhood Environment Rating Scale-Revised) and SSTEW (Sustained Shared Thinking and Emotional Well-being).The assessment of the condition of the sensory enriched environment was conducted by the 3rd year undergraduate students studying at the educational program «Preschool Education» at Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University, Mukachevo State University, Khmelnytskyi Humanitarian-Pedagogical Academy. At the stage of experimental activity, 21 experts, 30 educators were involved, 15 environments in preschool establishments were evaluated.The analysis of the main features of the external and internal sensory enriched environment, which was carried out on the basis of the proposed parameters of the ECERS and SSTEW scales, allows us to determine the features that set out the possibility of further enrichment of this environment. The authors propose to focus on the enrichment of the environment as a special means of integrating the accumulated pedagogical experience into a holistic pedagogical system, as well as the complexity of the child’s development situation, which is taken into account by adults.